Point and extended defect interaction in low – high energy phosphorus implantation sequences. (2018) - Mica, I.; Polignano, M.L.; Bacciaglia, P.; Brazzelli, D.; Cseh, D.; Galbiati, A.; Grasso, S.; Juhel, M.; Kiss, Z.T.; Monge Roffarello, P.; Tomezzoli, E.; Torti, A.M.
Abstract: The objective of this paper is to study the phenomenology of the extended defects generated by phosphorus (P) implantations in silicon with a special attention to the interaction with a previous implantation of the same specie already recovered by a furnace annealing. For this purpose we decided to analyze two P implantations: the first is shallower with a projected range of 110 nm and a dose high enough to amorphize the silicon, the second one is implanted after the furnace annealing of the first implantation and has a projected range of 1.4μm. For the deeper implantation different doses (from 1×10 13 to 1×10 14 cm -2 ) and two different schemes of annealing have been tested. More in depth there is a third P implantation with a projected range of 2.3μm and a dose in the order of some 10 13 cm -2 . Selective etching of silicon, transmission electron microscopy (TEM) and micro-photoluminescence, combined with secondary ion mass spectroscopy (SIMS) were used for the analysis of the implantation defects and for the determination of P distribution, respectively. Analyzing the two implantations separately we note that the shallower and amorphizing implantation left the dislocation loops aligned at the projected range, as expected; instead the couple of the deeper implantations shows the presence of threading dislocations which generate in the implanted zone (between 1 and 3μm) and which increase for many μm reaching the surface and also the deepest zone of the wafer (6.5μm). The situation changes if the implantations are done in the same sample, first the shallow implantation followed by the double implantations in depth. The dislocations are more numerous, but shorter. The interesting fact is that the growth of the defects is inhibited mostly towards the surface, while the zone affected by the defectiveness in depth remains more or less the same.